Polarization mode dispersion (PMD) in fiber optic / Fadhlina Mohd Nor - Mohd Nor, Fadhlina (2014)
Polarization mode dispersion (PMD), in single mode optical fibers, is phenomenon that can limit the bit-rate-distance product of amplified, light wave communication systems. In optical fibers, waveforms broaden over long distances, making these signals difficult to interpret by the time they reach the receiving end. The result is distorted data signals that results in transmission errors at the intended receiver. As network speeds and span lengths increase, dispersion becomes more severe. This applies to chromatic dispersion (CD) which occurs because different wavelength of light travel at different speeds-its subset, slope mismatch dispersion, and polarization mode dispersion (PMD), which is cause by light traveling faster in one polarization plane than another. Polarization mode dispersion, in high data rate systems, can significantly diminish the data carrying capacity of telecommunications network. A fundamental property of single mode optical fiber and component, Polarization Mode Dispersion (PMD) is a broadening of the input pulse due to a phase delay between input polarization states. The main objective of this project is to study and analyze the nature of the Polarization Mode Dispersion problems and the behaviors of the PMD in optical fibers. Next, the experiment and data collection will be doing at the optical fiber.